Test of writing for children in hindi - J, Kiran (Journal of All India Institute of Speech and Hearing)
The present study aimed at evaluating the patterns in the acquisition of writing in the primary school children. The test material prepared was given to the subjects ranging in age from 4-9 years, who were going to the schools where Hindi was a compulsory subject and whose mother tongue was Hindi. A range of writing skills were evaluated in these children. The results indicate that all the writing tasks other than copying are developing with age and the age of acquisition for different tasks vary.